Student’s Covariational Reasoning in Solving Covariational Problems of Dynamic Events - Sandie Sandie; Utin Desy Susiaty (JETL (Journal of Education, Teaching and Learning), 2020)
One of the reasons for learners to have poor covariational reasoning is because learners understand covariation to the extent that it is procedural, while conceptually it is not fully understood. The goal to be achieved is to describe the process of student covariational reasoning in constructing graphs. This research uses a qualitative approach. This type of research is qualitative research in which the main data is written and/or spoken words. The subjects in this study were odd semester students consisting of 3, 5, and 7 Mathematics Education Study Programs, Faculty of Mathematics, Natural Sciences and Technology IKIP-PGRI Pontianak. The research instrument consists of the main instrument, namely the researcher himself and the supporting instrument, namely the task of covariational problems in the form of a written test and interview guidelines. Data analysis by processing and preparing data from the assignment results to interpreting the data and making conclusions. This study examines the process of student covariational reasoning in solving dynamic incident problems. Students initially experience a pseudo error, however, along with the problem-solving process students can eliminate pseudo thinking that was initially experienced. Students have been able to solve covariational problems at Level 5, where these problems require students to be able to coordinate changes in the value of one variable against changes in the value of other variables. The problem at level 5 also requires students to be able to see changes in time and changes in water level that occur continuously by paying attention to the irregular shape of the bottle. The existence of the Covid-19 pandemic provides a limit for researchers in collecting data that should have been done directly online. This limits researchers to dig deeper into what students think in depth. The number of students who can solve this problem needs to pay attention to the IKIP PGRI Pontianak Institute to compile a curriculum or learning media that instils the concept of reasoning.